2017
DOI: 10.18632/oncotarget.21803
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the ALDH2 gene and the risk of ischemic stroke in a Chinese han population

Abstract: BackgroundPrevious studies have shown that aldehyde dehydrogenase 2 (ALDH2) plays a role in ischemic stroke progression. In recent years, the activation of the ALDH2 pathway have been reported serving as a useful index in the identification of stroke-prone participants, and the ALDH2 pathway may be a potential target for the therapeutic intervention in ischemic stroke.Materials and MethodsWe evaluated six tagging single-nucleotide polymorphisms (SNPs) of the ALDH2 gene in a case–control study from Hainan of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A meta-analysis of 83 prospective studies with 5,99,912 current alcoholic beverage drinkers mainly of European descent suggested that stroke incidence increased steadily with the alcohol intake [ 11 ]. This aligns with epidemiologic and genetic studies in China where U-shaped associations were found between self-reported alcohol intake and the incidence of ischemic stroke, intracerebral hemorrhage, and total stroke [ 12 , 13 ]. Moderate alcohol intake (100 g per week) was associated with a lower risk of stroke [ 13 ].…”
Section: Introductionsupporting
confidence: 84%
“…A meta-analysis of 83 prospective studies with 5,99,912 current alcoholic beverage drinkers mainly of European descent suggested that stroke incidence increased steadily with the alcohol intake [ 11 ]. This aligns with epidemiologic and genetic studies in China where U-shaped associations were found between self-reported alcohol intake and the incidence of ischemic stroke, intracerebral hemorrhage, and total stroke [ 12 , 13 ]. Moderate alcohol intake (100 g per week) was associated with a lower risk of stroke [ 13 ].…”
Section: Introductionsupporting
confidence: 84%
“…In contrast, Xu et al found that the prevalence of the G-allele of ALDH2 in the rs671 G>A polymorphism was higher in controls than in patients with IS, and stated that the A-allele and the GA genotype exerted protective effects against IS (A vs G, OR=0.37, 95% CI=0.19–0.72; GA vs GG, OR=0.30, 95% CI=0.14–0.65) 22. Other studies, such as those by Qu et al29 and Sun et al,28 did not find any significant relationship between the ALDH2 rs671 G>A polymorphism and IS risk.…”
Section: Discussionmentioning
confidence: 77%
“…Combining two data sources, we demonstrated the relationship between stroke and the rs12514417 polymorphism and its impact on alcohol consumption. Our main finding suggests that the ALDH7A1 rs12514417 TG + GG genotype may be associated with a 1.6-fold increased risk of ischemic stroke in subjects who drink more than 150 ml of alcohol per week[ 6 , 7 , 22 24 ]. This is the first study to identify the relationship between ALDH7A1 mutation and ischemic stroke, suggesting a change in lifestyle, specifically a reduction in alcohol consumption could reduce disease risk in carriers of this variant.…”
Section: Discussionmentioning
confidence: 99%